GENETIC MAPPING OF POTENTIAL QTLS ASSOCIATED WITH DROUGHT TOLERANCE IN WHEAT - S. Malik; Mehboob-ur-Rahman; T. A. Malik (Journal of Animal and Plant Sciences, 2015)
Water shortage is a major constraint to crop production in many parts of the world. Drought tolerance in wheat may be improved by manipulating and detecting quantitative trait loci (QTLs) related to drought tolerance. In the present project microsatellite markers were used for mapping QTLs for photosynthesis, cell membrane stability and relative water content in wheat. An F2 population derived from the intraspecific cross, Chakwal-86 (drought tolerant cultivar) x 6544-6 (drought sensitive genotype) was grown under drought stress in a hydroponic system. The correlation analysis revealed that net photosynthetic rate positively correlated with stomatal conductance, transpiration rate and cell membrane stability. Relative water content also positively correlated with cell membrane stability. Composite interval mapping detected one QTL for net photosynthesis, one for relative water content and two for cell membrane stability on the 2A wheat chromosome.  These QTLs may be used to tailor drought tolerant wheat through marker assisted selection or genetic engineering.
Keywords: QTLs; drought; wheat; cell membrane stability; net photosynthesis; relative water content